Community-Based Client Empowerment in Therapy Management of Type 2 Diabetes Mellitus Clients in the City of Surabaya - Adin Mu'firo; Irine Christiany; Kiaonarni Ongko Waluyo; Joko Suwito (Health Notions, 2021)
The Government of the Republic of Indonesia affirms its commitment to prevent and control diabetes through community empowerment. The research objective was to identify community-based client empowerment strategies in the management of client therapy with type 2 diabetes mellitus in the city of Surabaya. This type of research is a quasi-experiment using a pre-post test control group design. The research subjects were some of the diabetic patients in the Tambakrejo Health Center, Surabaya, totaling 80 people, divided into treatment and control groups. The independent variable is a community-based client empowerment strategy. The dependent variable is therapy management of DM clients. Data analysis using t-test. The results showed that there was an effect of Community-based Client Empowerment Strategies in the treatment group (p = 0.000≤α = 0.05) and the control (p = 0.078 ≥α = 0.05). At the pre-test, the mean of self-care management in the treatment group was 22.20 ± 6.65, while the control group was only 19.30 ± 5.27. There is a difference in the treatment group which has a delta mean of self-care management of 6.35 ± 7.66 and the control group of 2.28 ± 7.96. At the time of the pre-test the mean of self care management in the treatment group was 22.20 ± 6.65, while the control group was only 19.30 ± 5.27. The post-test the mean self-care management in the treatment group was 28.15±6.18, while the control group was 21.57±6.76Keywords: community; empowerment; T2DM; management-therapy;  health-promotion; nursing